Dispute Resolution of Breach of Contract in Loan Agreements - Ridho Syahputra Manurung (Fox Justi : Jurnal Ilmu Hukum, 2026)
The purpose of this study is to understand and analyze the resolution of default disputes in debt agreements. This type of research is normative with a legislative approach. The data used are secondary, consisting of primary and secondary legal materials. The research specification used is analytical descriptive. The resolution of default disputes in debt agreements can be concluded that the dispute resolution mechanism can be pursued through several legal channels, whether non-litigation, litigation, or alternative dispute resolution (ADR). Each channel has characteristics, advantages, and disadvantages that need to be considered accordingly the conditions and interests of the parties. The non-litigation route emphasizes deliberation and mutual agreement, the litigation route provides legal certainty through court decisions, while APS offers a flexible, efficient, and agreement-based solution. Therefore, it is recommended that the parties execute the agreement in good faith so as not to cause a breach of contract the conditions and interests of the parties. The non-litigation route emphasizes deliberation and mutual agreement, the litigation route provides legal certainty through court decisions, while APS offers a flexible, efficient, and agreement-based solution. Therefore, it is recommended that the parties execute the agreement in good faith so as not to cause a breach of contract.